A STUDY TO IDENTIFY FALL PREDICTION IN GERIATRIC POPULATION IN PESHAWAR - Shabbir, Rida; Farooqi, Salman; Jan, Mohammad Bin Afsar (Annals of Allied Health Sciences, 2016)
AIM: To determine risk of fall in geriatric population in the families of students of Institute of Physical Medicine & Rehabilitation, Peshawar. METHOD: It was a cross sectional survey performed in Institute of Physical Medicine and Rehabilitation Peshawar from Jan, 2014 to June, 2014. Students of IPM&R whose parents and grandparents were above the age of 65 were approached. Their parents and grandparents were analysed for the inclusion and exclusion criteria for fall prediction and those fulfilling the criteria were added in the study to identify risk of fall in them. They were analysed on Berg Balance Scale and scores were recorded according to low, moderate and high risk of fall. RESULT Total 81 males and 69 females participated in the study. Mean of Berg Balance scale showed majority of the population had scores from 21 to 40.22% of the people had high risk, 41% had moderate risk and 36.7% had low risk of fall showing that majority of people had moderate risk of fall. Total 76.7 % individuals were between the age group 65- 74. Medicine, age, gender, visual problems, reason of fall and ear problem have direct effect on score of Berg Balance scale (BBS). Age and gender were independent variables. Of the sample included. CONCLUSION: Berg Balance score falls with increasing age showing fall risk to increase with age and majority of people had moderate risk of fall. The survey triggered awareness among individuals about balance impairments. This will encourage them to take interventions to improve balance and to reduce the fall risk in future and to improve the quality of life.